(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
Today, a relevant and significant aspect of the complex and uncertain field of corporate finance is financial risk, especially market risk, understood as a measure of the maximum loss of a financial asset to an investment portfolio in a given period with a defined reliability. This risk is associated with financial crises with high impact of losses, postponing the development of nations and generating, with globalization, a weaker financial system in need of obtaining reliable and immediate information to make timely and accurate decisions. The present research has been collected from the sixties of the last century to the present, this journey shows the passage of several financial crises and their improvements. These events over time have produced a series of mathematical models, among which are: simple deterministic-stochastic models, VaR models and contemporary models of machine learning for predicting time series; in particular recurrent neural networks; the latter models of deep learning, not exclusive to the financial sector, need to be more accurate, parsimonious and flexible with respect to classical econometric models.